Particular characteristics of atopic eczema in tropical environments. The Tropical Environment Control for Chronic Eczema and Molecular Assessment (TECCEMA) cohort study (2017)
ABSTRACT: Background: Atopic dermatitis is a prevalent health problem in the world. Allergic sensitization is an important risk factor, but the roles of other factors, inherent in tropic region, are unknown. Objective: A cohort study was designed in a tropical city to investigate molecular and environmental risk factors for eczema, considering as particular features perennial exposure to mites, poor living conditions and others tropical characteristics. Methods: 433 patients were included at baseline and biological samples were collected during 24 months of follow-up. Clinical information was collected using questionnaires (SCORAD, DLQI and a subjective scale) during each clinical assessment. Results: The prevalence of atopic eczema was 93%, with similar frequency between children and adults; parents history of eczema and polysensitization to mites, dogs, cats, cockroaches and birds, were risk factors for severe and persistent eczema and allergic comorbidities. Food sensitization was present in 16% of patients but food-induced allergies were scarce. Psychiatric, dental and ocular disorders were the most frequent non-allergic comorbidities. Study limitations: selection bias. Conclusion: We presented a tropical cohort of patients with eczema and we identified some risk factors for severe and persistent dermatitis. Some patterns of sensitization were associated with severe eczema and respiratory symptoms, and the natural history of “atopic march” is different to that described in some industrialized countries. The collection of biological samples will contribute to the understanding of the gene/environment interactions leading to allergy inception and evolution.